2017
DOI: 10.18203/2394-6040.ijcmph20174237
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of knowledge of ASHA regarding child health services provided under NHM in Bhojipura block, District Bareilly

Abstract: Background: One of the key strategies under the National Rural Health Mission is having a community health worker who is an Accredited Social Health Activist (ASHA) for every village with a population of 1000. These ASHA workers should preferably be female, in the 25-45 years age group and have a qualification of at least eighth class. The knowledge about health services of ASHA is crucial for the success of National Health Mission. Methods: A cross sectional study was planned in Bhojipura village. Total 48 vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 1 publication
(1 reference statement)
5
11
1
Order By: Relevance
“…Only half of them (50.8%) responded there should be exclusive breastfeeding till six months after birth. In a study conducted by Saxena et al they found that only 23% of them knew about exclusive breastfeeding until six months after delivery [11].…”
Section: Discussionmentioning
confidence: 99%
“…Only half of them (50.8%) responded there should be exclusive breastfeeding till six months after birth. In a study conducted by Saxena et al they found that only 23% of them knew about exclusive breastfeeding until six months after delivery [11].…”
Section: Discussionmentioning
confidence: 99%
“…The figures were either equal or higher than the previous studies. 7,8,[11][12][13] As there was no new recruitment, with time and repeated training in between they were becoming more experienced and that might be the cause of their better knowledge. But this study found that only 34.21% had correct knowledge of updated IFA tablet dosage which was rather lower than that found by Choudary M et al Though they had poor knowledge about ECP, majority (56.84% and 70%) knew correctly about OCP and ideal time of IUCD insertion which showed a trend of improvement in their knowledge than found by Das A et al 5,10 Regarding practices, most of the beneficiary mothers (73.68 % and 84.21 %) were informed by ASHA workers about availability of JSY monitory support and JSSK transport support during institution deliveries.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies had been conducted in India on evaluation of their works, but in context of West Bengal there are scarcity of such researches specifically on maternal and child health domain. [5][6][7][8] Therefore, the current study had been taken up to assess the knowledge and practices of ASHA workers related to maternal-child health and family planning and to find out their performance affecting factors in a rural block of West Bengal.…”
Section: Introductionmentioning
confidence: 99%
“…Study conducted by Saxena S et al found that mostly 96.9% ASHA knew that breastfeeding should be given first to the new-born and 95.3% ASHA were known that breastfeeding should be initiated within one hour of delivery and 71.9%. 7 A study done by Paul, the knowledge of ASHAs about initiation of breastfeeding within an hour; feeding colostrum; avoiding pre-lacteal feeds and exclusive breastfeeding for six months was reported by 96 percent, 99 percent, 92 per cent and 98 percent of ASHAs. 10 On the other hand to this Shashank et al reported that 87.1% of ASHA educate about breastfeeding to the mother before the delivery and 100% of them educate the mother and advocated breastfeeding to the new born as soon as possible after delivery.…”
Section: In the Present Study 5286% Of Ashas Had Satisfactory Knowlementioning
confidence: 99%
“…In a study conducted by Saxena S et al found that 67.2% of ASHA replied that first visit should be conducted within one week of delivery followed by within 24 hour of delivery by 28.1% and no visit by 4.7% ASHA. 7 Kohli in their study concluded that only 67.3% ASHA workers reported that they used to visit the newborn in their area within a week of birth. 8 Another study carried out in Uttar Pradesh by Kansal et al found that 82% of ASHA workers used to visit newborns in the area.…”
Section: In the Present Study 6571% Of Ashas Visited Home Satisfactomentioning
confidence: 99%